MOBILE HEALTH DAN EFEKTIVITASNYA TERHADAP AKTIVITAS FISIK REMAJA: LITERATUR REVIEW - Fitriani Fitriani; Sigit Mulyono (Poltekkes Kemenkes Bandung, 2023)
Regular physical activity has many benefits for adolescents in the immediate and long-term. The high rate of obesity and low participation from adolescents in regular physical activity require strategies for lifestyle changes. The development of technology and innovation in health technology provides a strategy for increasing behavior change with smartphone applications (mHealth). This review aimed to identify the effectiveness of mHealth intervention strategies for facilitating physical activity among adolescents. The method used is the systematic search for literature review in electronic databases such as ProQuest, PubMed, Google Scholar, ClinicalKey Nursing, Scopus, SpringerLink and ScienceDirect with keywords mHealth and physical activities and adolescent” “smartphone apps and physical activities and adolescent” and “mobile applications and exercise and adolescent” on the years range 2018 to 2022. Only nine articles were kept for analysis from 1.861 articles found. This study states that mHealth has a positive effect on adolescent physical activity. The significant level of positive effect depends on the type of application used. Health workers can recommend mHealth as an intervention to increase adolescents’ physical activity.